Sociodemographic and personal factors related to depressive symptomatology in the Mexican population aged 12 to 65 Fatores sociodemográficos e pessoais relacionados à sintomatologia depressiva na população mexicana entre 12 e 65 anos - Clara Fleiz Bautista; Jorge Villatoro Velázquez; María Elena Medina Mora Icaza; Midiam Moreno López; María de Lourdes Gutiérrez López; Natania Oliva Robles (Brazilian Journal of Psychiatry, 2012)
OBJECTIVE: To describe the prevalence of depressive symptoms in the Mexican population, aged 12 to 65 years, by identifying the main related socio-demographic and personal factors. METHODS: Data are drawn from the National Survey on Addictions 2008 (ENA 2008), a random, probabilistic, multistage study. A randomly selected sub-sample of 22,962 persons answered the section on depressive symptomatology, measured with the Center for Epidemiologic Studies Depression Scale (CES-D). RESULTS: The total prevalence for depressive symptomatology was 5.1%; the prevalence was 7.5% for women and 2.5% for men. For women, more evidence of depressive symptoms was seen in the central region, whereas for men, symptoms were homogeneous across the country. Factors related to the presence of depressive symptoms include being divorced (in women) or widowed (in men), having lower educational attainment, perceiving one's place of residence as unsafe, displaying alcohol abuse or dependence, being a regular drug consumer (in men) and having been sexually abused (males and females). CONCLUSIONS: The regional distribution of depressive symptomatology in women indicates the need for region-specific prevention programs that take into account the different social problems that affect women's emotional well-being. More research is also needed to support the early identification and intervention of men suffering from depression. OBJETIVO: Conhecer a prevalência de sintomas depressivos a nível nacional na população de 12 a 65 anos e identificar os principais fatores sociodemográficos e pessoais associados. MÉTODO: Os dados foram obtidos da Pesquisa Nacional de Adições (ENA 2008), um estudo aleatório e probabilístico. Uma sub-amostra de 22.962 indivíduos responderam a seção de sintomas depressivos medida com a Escala de Depressão do Centro de Estudos Epidemiológicos (CES-D). RESULTADOS: A prevalência de sintomas depressivos foi de 5,2%; 7,5% em mulheres e 2,5% em homens. Entre as mulheres, os sintomas se apresentaram mais na região central do país e, entre os homens, a distribuição geográfica foi homogênea. Os fatores que se associaram aos sintomas depressivos foram estar divorciado (mulheres) ou viúvo (homens), ter nível educacional inferior, sentir sua residência como um local não seguro, apresentar dependência de álcool, ser usuário regular de drogas (homens) e abuso sexual. CONCLUSÕES: A distribuição regional de sintomatologia depresiva em mulheres indica a necessidade regional de orientação para prevenção, levando em conta que as distintas problemáticas sociais podem afetar seu bem-estar emocional. Entre os homens, mais estudos são necessários para identificação precoce da depressão.